Management of Candida guilliermondii joint infection in a dog. Issue 1 (December 2015) - Bufalari, Antonello; Maggio, Chiara; Moretti, Giulia; Crovace, Alberto; Stefanetti, Valentina; Straubinger, Reinhard; Passamonti, Fabrizio
Abstract Background Candida spp. are dimorphic fungi in the family Cryptococcaceae. Infections withCandida spp. are usually rare conditions in dogs, but immunocompromised patients have a higher risk for developing invasive candidal infections. Case presentation A 5-year-old male Boxer, positive toLeishmania infantum, was referred to the Veterinary Teaching Hospital of the Department of Veterinary Medicine, University of Perugia, Italy for examination of a non-weight bearing left hind limb lameness of a duration of at least 3 months. During this period, treatment involved systemic anti-inflammatory medications and intra-articular corticosteroid administration. On presentation, clinical examination and radiographic findings were suggestive of cranial cruciate ligament deficiency. To support this diagnosis a stifle arthroscopy was performed: it confirmed a partial rupture of cranial cruciate ligament. Samples culture of synovial fluid and membrane was routinely collected as well, and revealedCandida guilliermondii joint infection. Treatment for theC. guilliermondii joint infection involved systemic anti-fungal therapy, joint lavage and intra-articular administration of antifungal drugs. Lameness improved markedly during this treatment, but lameness did not resolve completely, probably due to cranial cruciate ligament deficiency. Tibial tuberosity advancement (TTA) was chosen in order to treat stifle instability and was performed 4 weeks following cessation of treatment of theC. guilliermondii joint infection. Six month after TTA the dog showed a completely recovery with no lameness. Conclusions To the authors' knowledge, this is the first case ofCandida spp. joint infection reported in dogs. The cause of the progression of the jointC. guilliermondii infection remains unclear but it may be associated with leishmaniasis or intra-articular corticosteroid injections. Treatment with systemic and intra-articular anti-fungal therapies was successful. In the evaluation of hind limb lameness in a chronically immunocompromised dog, it would be advisable to consider also an intra-articularCandida spp. infection.